Kaposi’s Sarcoma Associated Herpesvirus Entry into Target Cells - Chakraborty, Sayan; Valiya Veettil, Mohanan; Chandran, Bala (Frontiers in Microbiology, 2012)
Herpesvirus infection of target cells is a complex process involving multiple host cell surface molecules (receptors) and multiple viral envelope glycoproteins. Kaposi’s sarcoma associated herpesvirus (KSHV or HHV-8) infects a variety of in vivo target cells such as endothelial cells, B cells, monocytes, epithelial cells, and keratinocytes. KSHV also infects a diversity of in vitro target cells and establishes in vitro latency in many of these cell types. KSHV interactions with the host cell surface molecules and its mode of entry in the various target cells are critical for the understanding of KSHV pathogenesis. KSHV is the first herpesvirus shown to interact with adherent target cell integrins and this interaction initiates the host cell pre-existing signal pathways that are utilized for successful infection. This chapter discusses the various aspects of the early stage of KSHV infection of target cells, receptors used and issues that need to be clarified and future directions. The various signaling events triggered by KSHV infection and the potential role of signaling events in the different stages of infection are summarized providing the framework and starting point for further detailed studies essential to fully comprehend the pathogenesis of KSHV.